The media in Britain : current debates and developments - Stokes, Jane C.; Reading, Anna (St. Martin's Press ; Macmillan, 1999)
"The Media in Britain offers a timely and comprehensive review of the main contemporary debates in media studies, taking the reader through a range of empirical and analytical material in a highly structured and engaging way."--BOOK JACKET.